A Feasibility Study of Microfinance for Chinese Disabled Farmers - Pan Luo, Laura; Lin, Liu (Journal of MultiDisciplinary Evaluation, 2007)
The Chinese government supports development aid to persons with disabilities (PWDs) in the form of microfinance. The nation’s Poverty Alleviation and Development Plan for PWDs (2001-2010) and the Eleventh Five-Year Plan for Rural Disabled Persons (2006-2010) spell providing quality rehabilitation out that the main methods to help poor rural disabled persons include significantly increasing the amount of funds for their use as well as ion services for them. The local government at every level has the responsibility to assist disabled persons.